Creating neighbourhoods and places in the built environment - Chapman, David, 1947- (Built environment series of textbooks., 1996)
This design primer examines the forces at work in the built environment and their impact on the form of buildings and their environments. The actions of a range of individuals and agencies and the interaction between them is examined, exploring the competing interests which exist, their interaction with physical and environmental forces and the uncertain results of both individual and corporate intervention.